Instructor perceptions of effective teaching in LMOOCs and strategies utilized to enhance learner engagement - Matlack, Sara (AUC Knowledge Fountain, 2020)
The present study aims to investigate key strategies LMOOC instructors use to enhance learner engagement, their perceptions of effective LMOOC teaching, and the major challenges they face. A sequential mixed methods approach using quantitative and qualitative methods was used. A sample of ten LMOOC instructors participated in the online questionnaire and four interviews were conducted. Content analysis on four top rated LMOOCs was conducted to further validate engagement strategies used. Quantitative results were analyzed using descriptive statistics. Qualitative data was divided into themes. The results concluded that the top three engagement strategy themes were interaction, participation, and content. Overall, LMOOC instructors perceived their role as an instructor, previous training and teaching experiences, pedagogies and content important to the effectiveness of their LMOOC. Instructors perceived LMOOCs to be effective in language learning, yet perhaps not as effective as a traditional language classroom. The most common challenges that were supported by both the online questionnaires and the instructor interviews were: pedagogical and platform limitations, variation of learners’ background and proficiency level, dropout rate, and engagement of learners. This research paper has ultimately contributed to the lack of studies on LMOOCs, coverage of instructors’ perceptions literature, and potential future influences of LMOOCs into the current online education situation and help better prepare instructors and educational policy makers of future course offerings.